Developing circular concrete: Acid treatment of waste concrete fines. (10th September 2022) - Ding, Tiejun; Wong, Hong; Qiao, Xiuchen; Cheeseman, Christopher
Abstract: The development of circular concrete, to enable key components to be extracted and reused, is a key requirement to achieve sustainability in the built environment. Current industry practice for end-of-life concrete is best described as down-cycling because recycled concrete aggregate has limited use, with disposal of the associated crushed concrete fines. Acid treatment of waste concrete is being investigated to allow key concrete components to become circular and, in this work, the effect of acetic acid concentration, liquid/solid (L/S) ratio, reaction time and temperature on the leaching of waste concrete fines is reported. An acid concentration of 0.6 mol/L, an L/S ratio of 7 ml/g, and a reaction time of 6 h at ambient temperature allows clean sand to be extracted from concrete fines. This performs identically to new sand in mortar samples. We show for the first time that the dried and ground silica-rich residue produced by acid leaching has pozzolanic properties comparable to commercially available supplementary cementitious materials (SCM) such as blast furnace slag and coal fly ash. The potential for CO2 sequestration using the Ca 2+ - rich leached solution to form CaCO3 is calculated. The research shows that acid leaching of concrete fines can produce clean reusable sand, generates a viable SCM and sequester significant amounts of CO2 by forming precipitated calcium carbonate.